EKSPEKTASI MAHASISWA TERHADAP PELAYANAN AKADEMIK PROGRAM STUDI PENDIDIKAN AGAMA ISLAM FITK UIN RADEN FATAH PALEMBANG - Zulhijra Zulhijra (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2019)
The success of the study program (Prodi) as a work unit in higher education is largely determined by the quality of services provided, where quality services can be identified through the satisfaction of service users, in this case students. Academic problems that are often encountered are related to the presence of lecturers in teaching. This academic service is also one of the usual problems faced by students in the teaching and learning process. For example, often the inaccuracy of the lecturer is present or completed in the teaching and learning process and that of course makes students uneasy and has to wait more than the hours specified by the study program. In addition, there is no maximum availability of facilities and infrastructure to support the learning process, such as a minimal LCD and when used as a projector in teaching it is damaged so the lecture process is slightly hampered. The formulation of the problem of this research is, How is the academic service provided by the PAI FITK Study Program UIN Raden Fatah Palembang? What are the constraints of academic service in the PAI FITK Study Program UIN Raden Fatah Palembangin? order to improve the quality of academic services? This type of research is qualitative research with a descriptive approach. Data collection techniques used in this study: observation, interviews, and documentation. This study uses qualitative descriptive data analysis techniques that describe, describe, and explain the data obtained from the results of the study, then concluded as a result of the analysis. From the results of the study, students' expectations of academic services at PAI FITK UIN Raden Fatah Palembang were not in line with expectations. The constraints faced in the academic service in the Islamic Education Department of Raden Fatah Palembang State Islamic University are: Academic service Prodi still seems slow, facilities and infrastructure are inadequate and still need to be completed, both quantity and quality human resources are still far from expectations so service is not maximized, There is still a lack of discipline among employees. Various efforts have been made: In terms of facilities and principles, continuous improvements are made so that the lecture process and academic services run well, Supervise internal employees and evaluate employee performance in order to improve the quality of performance, increase quantity and provide training to employees to maximize performance. Giving rewards to employees who excel in their fields so that they can motivate other employees to boost and improve their performance even better than before.